Textual Analysis of Annual Reports and Company Performance in a Market Perspective - Ana Putri Fauziah; Moh Yudi Mahadianto; Mada Purwanto W.N (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research looks at the connection between a company's financial success and the tone it uses in its annual reports, specifically how an optimistic tone in the MD&A affects the market reaction. Included in the sample are 25 non-financial firms that were listed on IDX30 between 2020-2024. Natural Language Processing (NLP) text mining methods and panel data regression with an event study methodology were used to perform the investigation. The findings provide credence to signalling theory and market efficiency by demonstrating that an optimistic tone significantly impacts Cumulative Abnormal Return (CAR). Companies that have done well financially (high ROE) also have a tendency to sound more hopeful, which is consistent with agency theory. These results prove that annual report narratives are more than just filler; they are powerful instruments of strategic communication that shape how the market perceives a company. Credible and informative narrative disclosures are needed in financial reports, according to this research, which adds to the literature on developing markets.